Myasthenia gravis and autoimmune overlap: Prognostic insight - Emel Oguz-Akarsu; Sarra El hamida Lazrak; Deniz Sigirli; Gizem Gullu; Yasemin Dinç; Furkan Saridas; Necdet Karli (PLoS ONE, 2025)
Background Autoimmune diseases (ADs) frequently coexist with myasthenia gravis (MG), suggesting shared genetic and immunological mechanisms. However, the impact of comorbid ADs on MG prognosis remains unclear. This study aimed to investigate the prevalence, clinical characteristics, and prognosis of MG patients with comorbid ADs in a Turkish cohort. Methods We retrospectively analyzed 302 MG patients treated at a tertiary center between 2010 and 2024. Patients were grouped based on the presence of comorbid ADs. Clinical characteristics, disease severity, treatment response, and prognosis were compared. Results Among 302 MG patients, 41 (13.6%) had at least one comorbid AD, with autoimmune thyroid disease (AITD) being the most common (10.6%). ADs were more frequent in females. Patients with and without comorbid ADs showed no significant differences in MG severity, thymectomy rates, myasthenic exacerbations, or overall outcomes (p > 0.05). However, female patients with ADs experienced more frequent myasthenic exacerbations and had a higher rate of rituximab use (p < 0.05). Conclusions Comorbid ADs do not significantly impact MG severity or prognosis. Female MG patients with ADs have a higher frequency of myasthenic exacerbations and rituximab use, warranting further research. Early identification of ADs remains essential for optimal patient management.